Polymer Chain Reaction (PCR): Principle and Applications - Shafeeq, Noorhan Khalid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The new, standard molecular biologic system for duplicating DNA enzymatically devoid of employing a living organism, like E. coli or yeast, represents polymerases chain reaction (PCR). This technology allows an exponential intensification of a minor quantity of DNA molecule several times. Analysis can be straightforward with more DNA available. A thermal heat cycler performs a polymerization chain reaction that involves repeated cycles of heating and cooling the reactant tubes at the desired temperature for each reaction step. A heated deck is positioned on the upper reaction tube to avoid evaporating the reaction mixture (normally volumes range from 15 to 100 l per tube), or an oil layer can be placed on a reaction mixture surface. The amplified DNA fragment is determined based on selecting primers in addition to the starting and end of the DNA fragment. The primers stand for short, artificial DNA stripes, no higher than fifty (typically 18-25bp) nucleotides have been based on a starting and ending of DNA fragment to be amplified. DNA-polymerase connects and starts a new DNA strand synthesis The PCR products can be visualized by dual foremost methods: (1) staining of the product of DNA amplified by a chemical dye like bromide ethidium, or (2) marking of fluorescent dyes (fluorophores) PCR primers or nucleotides before amplification of PCRs. PCR offers some benefits. First, it is a simple method of understanding and using and quick results. It has an extremely sensitive technology with the potential for sequencing, cloning, and analyzing millions or milliards of copies of a particular product.